2021
DOI: 10.1021/acs.jafc.0c08040
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Strategy for Purification by Combining Solid-Phase Extraction with Dispersive-Solid-Phase Extraction for Detecting 22 Pesticides and Metabolite Residues in Fish

Abstract: A robust isotope-labeled internal standard method was established for the detection of 22 pesticides and metabolite residues in four kinds of fish; two were from freshwater fish, and two were from marine fish. Pesticides with wide application possibilities in rice in China, strong leaching to water, or high bioconcentration factors (BCF) in fish were selected. The samples were extracted with 1% acetic acid−99% acetonitrile. The extracts were first purified by solid-phase extraction (PEP-plus), cleaned with dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…According to the general requirements stated in document SANTE/11312/2021, 22,23 the method was validated, encompassing linearity, sensitivity, recovery, repeatability, and matrix effects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the general requirements stated in document SANTE/11312/2021, 22,23 the method was validated, encompassing linearity, sensitivity, recovery, repeatability, and matrix effects.…”
Section: Methodsmentioning
confidence: 99%
“…The addition of a suitable amount of formic acid to the extraction solvent can improve the recovery rate. 22,27 In this study, three extraction solvents, methanol, ACN, and 0.2% formic acid in acetonitrile, were compared to select the appropriate extraction solvent. The results showed that the recovery rate of methanol as extraction solvent was lower than 50% for most pesticides, while the recovery rate of cypermethrin, beta-cypermethrin, and difenocarb was higher than 120% when 0.2% FA was used.…”
Section: Optimization Of Uplc-ms/ms Conditionsmentioning
confidence: 99%
“…Inter‐day RSD was calculated using all recoveries determined on three continuous days at three spiked levels [27]. The absolute and relative recoveries were calculated according to Equations () and () [29]: Absoluterecovery=AnalyteresponsefromextractAnalyteresponsefromstandard×100%\begin{eqnarray} && {\rm{Absolute\;recovery}}\nonumber\\ &&\quad = \frac{{{\rm{Analyte\;response\;from\;extract}}}}{{{\rm{Analyte\;response\;from\;standard}}}} \times 100\ {\rm{\% }}\end{eqnarray} Relativerecovery=false(Analyteresponsefromextractfalse)/false(ISresponsefromextractfalse)false(Analyteresponsefromstandardfalse)/false(ISresponsefromstandardfalse)×100%\begin{eqnarray} &&\text{Relative}\ \text{recovery}\nonumber\\ &&\quad=\frac{ \def\eqcellsep{&}\begin{array}{c} (\text{Analyte}\ \text{response}\ \text{from}\ \text{extract})/\\ (\text{IS}\ \text{response}\ \text{from}\ \text{extract})\end{array} } { \def\eqcellsep{&}\begin{array}{c}(\text{Analyte}\ \text{response}\ \text{from}\ \text{standard})/\\(\text{IS}\ \text{response}\ \text{from}\ \text{standard})\end{array} }\times 100{\rm{\% }}\end{eqnarray}…”
Section: Methodsmentioning
confidence: 99%
“…As IMI and its metabolites have the same constitutional formula as IMI-D 4 , the same performance was obtained during the extraction and clean-up procedures. In liquid chromatography analysis, the analytes would elute at a similar retention time and calibration with internal standards yields satisfactory results [29,43].…”
Section: Matrix Effectmentioning
confidence: 99%
“…As for the currently used pesticides, a comparison of the method with other methods in terms of analyte species, analysis time, sample pretreatment method, and LOQs is shown in Table 1 . Previous research has focused on a limited number of pesticides [ 19 , 20 , 21 , 22 ] or has been restricted to a certain class of pesticides, such as pyrethroids pesticides [ 23 ], organofluorine pesticides [ 24 ], and triazine herbicides [ 25 ], which is a disadvantage for the large-scale screening of pesticide residues in aquatic products. In this study, 90 pesticides and metabolites were selected, including 45 insecticides, 18 fungicides, 23 herbicides, 2 plant growth regulators, and 2 acaricides.…”
Section: Introductionmentioning
confidence: 99%